Effect of Endectocides and Antibiotic Dung Poisoning on Mortality of Dung Beetle Species: Antibiotic Dung Poisoning in Diferent Species (Biological Sciences - PJSIR, 2021)
We explored the effect of endectocides (deltamethrin and trichlorophenol) and antibiotics (enrofloxacin and oxytetracycline) on dung beetle species, 0nthophagus gazella and 0nitis excavatus under laboratory conditions. 0. gazella and 0. excavatus were collected from pastures and crop lands of Jhelum, Punjab, Pakistan. The selected endectocides and antibiotics were applied on dung pats placed over soil @ 0.25, 0.50, 0.75 and 1 ppm and kept in glass containers of 2' x 2' x 1.5' size. The laboratory bioassay was carried out at 28 ± 2 °C temperature and 65 ± 5 % RH with 12:12 of light to darkness ratio. Our results demonstrated that deltamethrin, trichlorophenol and oxytetracycline were toxic to both species, 0. gazella and 0. excavatus after two weeks of the exposure. Comparatively higher dung beetle mortality was recorded in both deltamethrin and trichlorophenol when applied @ 1 ppm as compared to 0.25, 0.50 and 0.75 ppm concentrations in 0. gazella and 0. excavatus showed significantly higher mortality against oxytetracycline (53.3 % and 93.3 %, respectively), trichlorophenol (80 % and 94 %, respectively) and deltamethrin  (88% and 76 %, respectively) at 1 ppm concentrations, whereas no mortality was recorded in all concentrations of enrofloxacin. 0. gazella and 0. excavatus responded negatively to the presence of different concentrations of veterinary parasiticides. In addition to the hazardous effect of 0. gazella and 0. excavatus, the study reports that these dung beetle species can be exploited as bio-indicators for environmental assessment in ecosystem studies.